THE IMPACT OF PUBLIC SENIOR AND VOCATIONAL HIGH SCHOOL ADMISSION QUOTA EXPANSION ON PRIVATE SCHOOLS A CASE STUDY OF SMK BUDI BAKTI UTAMA - Adang Sukanda; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
The expansion of public senior and vocational high school admission quotas in West Java has significantly affected the sustainability of private educational institutions. This study aims to analyse the impact of the policy and examine the adaptation strategies implemented by SMK Budi Bhakti Utama. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document analysis involving school administrators and institutional records. The findings reveal that the optimization of class capacity in nearby public schools has substantially reduced the number of new student enrolments in the private school. The total student population decreased from 267 students in the 2023/2024 academic year to 233 students in 2025/2026. This decline directly affected the allocation of School Operational Assistance (BOS) funds and forced the institution to implement strict budget efficiency measures. The situation was further exacerbated by prospective students withdrawing their registration after being accepted into public schools. In response, the school adopted several adaptation strategies, including the development of a Content Creator curriculum, expansion of partnerships with retail industries, and the elimination of building fees. The study concludes that the public-school quota expansion policy has created significant managerial challenges for private schools and requires continuous innovation and institutional transformation to maintain competitiveness and sustainability.